Adesividade Agregado-Ligante: efeito no comportamento de misturas asfálticas e na previsão de desempenho de pavimentos - Lucas Júnior, Jorge Luiz Oliveira (2021)
Numerous researches have already identified that the neat asphalt binder may not produce the proper quality of the asphalt mixture when it contains acid aggregates, due to the poor aggregate-binder adhesiveness. An alternative to improve this property is to use an anti-stripping agent. Therefore, the objective of this work was to determine how the aggregate-binder adhesiveness affects the mechanical behavior of asphalt mixtures and consequently the prediction of pavement performance. Four scales were analyzed: separate binder and aggregate, aggregate-binder adhesiveness, asphalt mixture, and pavement structure. In addition to the basic tests themselves, 1 method for evaluating the morphological properties of the aggregates, 1 innovative method for evaluating the properties of mixtures based on digital image processing, 2 types of tests on asphalt binders, 3 different aggregate-binder adhesion tests, 4 different tests on asphalt mixtures, and 2 computer programs for analysis and design of asphalt pavements. This thesis is organized as a compendium of papers, including articles already published and others submitted to journals. Paper 1 addresses the effects of aggregate shape properties and the adhesion of the binder to the aggregate on the results of the compression and tension/compression tests in hot asphalt mixtures. Paper 2 assesses the effect of an amine-based anti-stripping agent on the fatigue life of pavements. Paper 3 presents the effect of temperature, thickness, load and speed in predicting cracked areas of asphalt pavements. Paper 4 deals with the effect of rheology and the adhesiveness of asphalt binders to different substrates on resistance to moisture conditioning. In paper 1, adhesiveness was indicated as more important than aggregate morphology for fatigue measured using tension-compression, while the type of aggregate proved to be more important for compression tests. In paper 2, mixtures with an amine-based anti-stripping agent showed a longer fatigue life when compared to mixtures with a neat binder. In paper 3, each variation of ± 1cm in the thickness of the asphalt surface course produced in the cracked area an effect similar to variations of ± 1.1ºC, ± 5.6km/h or ± 16.6kN of load per single wheel axle. In paper 4, although the additive improved the adhesive properties of the binder to the aggregate, it caused an average reduction of 9.5% in the binder stiffness in the dry condition, and 8.7% after moisture conditioning and less resistance to permanent deformation at 82ºC.